2011
DOI: 10.3928/00220124-20110502-02
|View full text |Cite
|
Sign up to set email alerts
|

Disaster Preparedness for Nurses: A Teaching Guide

Abstract: As one of the largest groups of health care providers in the United States, nurses are trained to attend to the physical, psychological, and spiritual needs of their patients, making them highly qualified to influence the outcomes of victims of an emergency situation. Unfortunately, nursing programs offer limited content on delivering care under extreme conditions, and few continuing education programs are available to practicing nurses. This article provides a brief educational presentation that can be used w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…compassion, adaptability, critical thinking and organizational ability), and possess a comprehensive range of clinical skills and knowledge across domains of acute care, public health, advocacy, community resources and mental health. There is evidence in the literature that registered nurses hold similar notions of the roles and responsibilities of disaster nurses to those held by participants in this research (Al Khalaileh, Bond, & Alasad, 2012;American Nurses Association, 2008;Arbon, Bobrowski, Zeit, Hooper, Williams, & Thitchener, 2006;Fung, Loke, & Lai, 2008;Ireland, Ea, Kontzamanis, & Michel, 2006;JenningsSanders et al, 2005;Nasrabadi, Naji, Mirzabeigi, & Dadbakhs, 2007;Slepski, 2007;Tichy, Bond, Beckstrand, & Heise, 2009;Tillman, 2011;Usher, 2010;Yang, Xiao, Cheng, Zhu, & Arbon, 2010). Conversely, the literature reporting on nursing undergraduates found that few respondents identified clinical roles for disaster nurses, a finding at odds with those of this study (Jennings-Sanders et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…compassion, adaptability, critical thinking and organizational ability), and possess a comprehensive range of clinical skills and knowledge across domains of acute care, public health, advocacy, community resources and mental health. There is evidence in the literature that registered nurses hold similar notions of the roles and responsibilities of disaster nurses to those held by participants in this research (Al Khalaileh, Bond, & Alasad, 2012;American Nurses Association, 2008;Arbon, Bobrowski, Zeit, Hooper, Williams, & Thitchener, 2006;Fung, Loke, & Lai, 2008;Ireland, Ea, Kontzamanis, & Michel, 2006;JenningsSanders et al, 2005;Nasrabadi, Naji, Mirzabeigi, & Dadbakhs, 2007;Slepski, 2007;Tichy, Bond, Beckstrand, & Heise, 2009;Tillman, 2011;Usher, 2010;Yang, Xiao, Cheng, Zhu, & Arbon, 2010). Conversely, the literature reporting on nursing undergraduates found that few respondents identified clinical roles for disaster nurses, a finding at odds with those of this study (Jennings-Sanders et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Turkey developed a system for disaster and emergency management using lessons learned from the devastating earthquake in 1999 (WHO/Europe, 2013). However, few schools of nursing have yet identified important obstacles for curricula, and may also include faculties that are insufficiently prepared to teach this subject matter (Tillman, 2011;Wisniewski, Dennik-Champion, & Peltier, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Training and education have long been accepted by researchers in disaster response as an essential part of disaster preparedness (Chapman & Arbon, ). Unfortunately, nursing programs offer limited content on delivering care under extreme conditions, and few continuing education programs are available to practicing nurses (Tillman, ). It is accepted that any event resulting in mass casualties will exceed the number of healthcare workers who will be able to supply care (Ünlü, Kapucu, & Şahin, ).…”
Section: Introductionmentioning
confidence: 99%
“…The information found in the published work consists primarily of qualitative, non‐experimental, descriptive research. Considering that disaster nursing has only recently become a prevalent topic in the nursing profession, limited research of any type is difficult to find (James & Duarte, ; Tillman, ).…”
Section: Introductionmentioning
confidence: 99%